Formulation and characterization of cosmetic cream incorporating piper Betle Linn. extract - Hanif, Nadzira; Doolaanea, Abd Almonem; Ab. Hadi, Hazrina (2017)
INTRODUCTION: Piper betle Linn. is an evergreen and perennial plant with glossy heart-shaped leaves which contains various biologically active compounds. Hydroxychavicol is a phenolic compound found in Piper betle leaves which exhibits many potential biological activities such as antimicrobial, antioxidant, anti-inflammatory and anti-tyrosinase.OBJECTIVES: The study aimed to formulate cosmetic cream incorporating Piper betle extract and to characterize the developed cream.METHODS: The cosmetic cream containing 0.02% Piper betle extract was developed by incorporating three phase ingredients include aqueous phase (75.2%), oil phase (20.8%) and cooling phase (4.0%). O/W emulsion was prepared by adding aqueous phase into oil phase through a combination process of heating up to 75℃ and homogenization at 3500 rpm. The cream formulation was characterized for organoleptic properties, pH, particle size, zeta potential, rheological behaviour and microbial limit test.RESULTS: For organoleptic properties, the cream has an off white color, pleasant odour, smooth texture and no phase separation. The cream formulation has a pH value of 5.39 ± 0.03 which was near to skin pH (4.5-5.5), smaller particle size of 3.73 ± 0.01 µm and polydispersity index of 0.56 ± 0.11, negatively zeta potential of -57.53 ± 1.47 mV and exhibited non-Newtonian behavior in which viscosity decreases when shear rate increases. The cream has no growth of viable microorganisms, yeasts and fungi.CONCLUSION: Based on physical characterization, the cream containing 0.02% Piper betle extract is regarded as a stable formulation with acceptable organoleptic properties.Keywords: Characterization, cream, formulation, oil in water emulsion, Piper betle Linn.